2020
DOI: 10.3390/ijms21228879
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of Mitochondrial Ribosomal Proteins and Their Encoding Genes with Cell Apoptosis and Diseases

Abstract: Mammalian mitochondrial ribosomes translate 13 proteins encoded by mitochondrial genes, all of which play roles in the mitochondrial respiratory chain. After a long period of reconstruction, mitochondrial ribosomes are the most protein-rich ribosomes. Mitochondrial ribosomal proteins (MRPs) are encoded by nuclear genes, synthesized in the cytoplasm and then, transported to the mitochondria to be assembled into mitochondrial ribosomes. MRPs not only play a role in mitochondrial oxidative phosphorylation (OXPHOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 133 publications
(185 reference statements)
3
76
0
Order By: Relevance
“…In contrast, the identified genes, including mitochondrial ribosomal protein s14 (MRPS18), 15, and 21, were downregulated by exposure to HgCl 2 in H1299 cells. Recent findings regarding the mitochondrial ribosomal protein reported that the dysregulated MRPs (Mitochondrial ribosomal proteins) affects mitochondrial metabolism disorder, cell dysfunction leading to apoptosis [ 34 ]. Furthermore, mercury ions specifically blocked synthesis of ribosomal RNA whereas activity of RNA polymerase II remained unchanged [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the identified genes, including mitochondrial ribosomal protein s14 (MRPS18), 15, and 21, were downregulated by exposure to HgCl 2 in H1299 cells. Recent findings regarding the mitochondrial ribosomal protein reported that the dysregulated MRPs (Mitochondrial ribosomal proteins) affects mitochondrial metabolism disorder, cell dysfunction leading to apoptosis [ 34 ]. Furthermore, mercury ions specifically blocked synthesis of ribosomal RNA whereas activity of RNA polymerase II remained unchanged [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple regulators of the intrinsic apoptotic pathway, recent studies have reported the involvement of some MRPs [ 71 ].…”
Section: Role Of Ribosome Biogenesis In Neoplastic Transformationmentioning
confidence: 99%
“…The oncogenicity of bS16m (MRPS16) and mL42 in the development of glioma has been recently demonstrated. In particular, the overexpression of bS16m promotes the migration and invasion of glioma cells by activating PI3K/Akt/Snail axis [ 71 , 91 ].…”
Section: Role Of Ribosome Biogenesis In Neoplastic Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…High MRPL13 promoted invasion in liver cancer cells (16). Apart from participating in mitochondrial oxidative phosphorylation (OXPHOS), the new roles for MRPs in cellular apoptosis and proliferation have been revealed (17). Actually, research has declared that MRPS29 promotes apoptosis through its interactions with Fas ligand (18).…”
Section: Introductionmentioning
confidence: 99%